Brown-eyed leaders of the sun : a portrait of Latina/o educational leaders - Hernandez, Frank (College dean); Murakami, Elizabeth (Emerald Publishing Limited : IAP, Information Age Publishing, Inc., 2016)
This volume focuses on the important relationship between racial and ethnic identity and requirements for Latino/a educational leaders today. As the racial and ethnic diversity of communities continues to rise, there is an increasing need for the diversification of school leaders who can improve student success, retention, engagement, and successful academic achievement. This entails a deeper understanding about the role/definitions of leadership among communities of color, leadership succession, the importance of gender/ethnic differences, as well as methods for recruitment, retention and development of school administrators and other school leaders of color in education. Latina/o school leaders, their personal histories, leadership challenges related to gender and race, contributions, roles, responsibilities, and career aspirations, both personal and organizational, are undocumented in the school leadership research.A study of Latina/o leaders that examines leadership experiences, the relationship between leadership and identity, and career aspiration offers important dimensions for the field of educational leadership. For these reasons, examining Latina/os and school leadership is both timely and relevant to our K-12 schools, educational leadership programs, and changing demographics. The secondary purpose of this publication is to enrich the preparation of school administrators of color, as to the skills and knowledge necessary to serve the needs of students in contemporary times.
Keywords: Hispanic Americans -- Education -- Social aspects.; Hispanic American educators.; Educational leadership -- United States.; Education -- Multicultural Education.; Ethnic studies.; Educational strategies and policy.; Ethnic groups and multicultural studies.; elektronické knihy; electronic books